Harnessing the Potential of Bacteriocin in the Treatment of Typhoid Fever and Cholera: A Systematic Review - Samson Baranzan Wayah; Atika Abubakar-Garba Faila; Peter Ojodale Adejo; Mariya Abubakar Balarabe; Zaharaddeen Abdullahi (Ibom Medical Journal, 2025)
Background: Typhoid fever kills 135,000 to 230,000 people every year and affects an estimated 11–21 million people globally. About 95,000 people die annually from cholera, and an additional 2.86 million get infected. Bacteriocins have been reported to inhibit the growth of various pathogens such as Salmonella typhi and Vibrio cholerae.